A MODEL FOR DEVELOPING PROFESSIONAL ETHICS AND PEDAGOGICAL CULTURE IN FUTURE TEACHERS - Kazakov Shavkat Norqobilovich (Bright Mind Publishing, 2025)
The article examines the urgent need to cultivate moral maturity, professional ethics, and pedagogical culture among future teachers in the context of globalization and digital transformation. It argues that educators must transcend the role of knowledge transmitters to become moral leaders, cultural role models, and ethical guides for students. The study highlights that the teacher’s personal integrity, justice, empathy, and responsibility significantly influence the formation of students’ values, worldviews, and civic positions. Moral maturity is defined as an inner state of self-discipline, justice, fairness, and adherence to universal human values, which are essential for building socially responsible and ethically stable societies. Higher education institutions play a central role in ensuring that future teachers acquire not only academic knowledge but also the ability to embody moral principles in their professional and personal interactions. To achieve this, the research proposes a scientifically grounded, modular pedagogical model designed to integrate goal-setting, content development, technological methods, and diagnostic mechanisms into a coherent system. This model ensures systematic formation of ethical standards and pedagogical culture, reinforcing the broader goal of preparing educators who can meet the moral and cultural needs of contemporary society.
Keywords: Moral maturity, professional ethics, pedagogical culture, teacher education, values, higher education, ethical leadership, pedagogical model.